Sosialisasi Pentingnya Pendidikan Untuk Mengurangi Tingkat Pernikahan Dini di Desa Banding Agung - Rina Oktaviana; Leni Widiyanti; Itryah (Forum Kerjasama Pendidikan Tinggi, 2022)
Education is a process of learning the knowledge, skills, and habits of a group of people passed down from one generation to the next through a system of training, guidance and research to create a superior generation in the future. Meanwhile, early marriage is a great institution to bind two people of the opposite sex who are still underage teenagers in one family bond (Lutfiati, 2008: ). Economic factors are often accompanied by the level of education. The lower the level of education and knowledge of a teenager, especially those who drop out of school, the higher the probability that these teenagers will be married prematurely. Therefore, there is a need for socialization to increase knowledge and knowledge and remind the importance of education for the younger generation in the future with the aim of this socialization being able to reduce the number of early marriage rates in Banding Agung Village